The Deep Faults in Kut-Hai and Surrounding Area Inferred From Gravity and Magnetic Data - AL-Banna, Ahmed S .; Daim , Falih M.; Daim , Falih M.; AL-Zubaidi, Ali .A.M. (Iraqi Journal of Science, 2021)
Gravity and magnetic data are used to study the tectonic situation of Al-Kut- Al-Hai and surrounding areas in central Iraq. The study included application of manyprocessing and interpretation programs. The window method with different spacingwas used to separate the residual from regional anomalies for gravity and magneticdata. The Total Horizontal Derivative (THDR) techniques used to identify the faulttrends in the basement and sedimentary cover rocks depending upon gravity andmagnetic data. The identified faults in the study area show (NW-SE), (NE-SW) (NS)and (E-W) trends. It is believed that these faults extending from the basement tothe upper most layer of the sedimentary cover rocks.